Delayed Amplatzer Occluder Device Closure of Postinfarction Ventricular Septal Defect: A Case Report - Francis Ting; Aditya Bhat; Neville Sammel; David Muller (Case Reports in Cardiology)
Postinfarction ventricular septal defect (VSD) is a rare complication after acute myocardial infarction, with an incidence rate of 1-2% of all myocardial infarcts (Hutchins, 1979). It is a medical emergency with sobering survival numbers, having a mortality rate of 70–80% within two weeks of the incident event (Bouchart et al., 1998). Cardiac surgery is considered the gold standard in the management of these defects; however, its main limitation is that it carries a high risk of perioperative mortality and postoperative sequelae. Percutaneous transcatheter closure of VSD is a relatively new method of repair. Due to scarcity of reports in the literature, there is limited data regarding survival data; however, noninferiority to surgery has been demonstrated in one case series (Papalexopoulou et al., 2013). Long-term follow-up studies are lacking, and thus long-term mortality has yet to be discerned. We present a case of an 87-year-old female who, following postmyocardial infarction VSD, developed clinically significant heart failure. The patient was reluctant to undergo open repair given her age and comorbidities and she underwent successful percutaneous repair of her VSD using a 16 mm Amplatzer occluder device 18 months after her initial presentation.